Morfološka variabilnost lesnike (Malus sylvestris (L.) Mill.) v Sloveniji in smernice za njeno dolgoročno ohranitev - Kišek, Mateja (Gozdarski vestnik, 2015)
European crab apple (Malus sylvestris (L.) Mill.) is indigenous and relatively poorly studied tree species in Slovenia. Through detailed morphometric analysis, we examined 97 trees from 9 populations. Based on the most appropriate morphological characters for identification of European crab apple, hairiness of leaves and diameter of fruits, only 44% of 36 analyzed trees represented European crab apple. Other trees are potential hybrids of European crab apple (Malus %domestica Borkh.) or feral cultivars. Our results show that European crab apple is a rare and potentially vulnerable tree species in Slovenia. Reliable identification is the most important for successful preservation. The most appropriate traits for determination are hairiness of leaves (hairless leaves) and fruit diameter (equal or less than 35 mm). Typical are also yellow color of the fruit without red color. In order to successfully preserve European crab apple, more attention should be paid to cultivation measures. It is essential to provide verified and certified forest reproductive material.
Keywords: lesnika; Malus sylvestris (L.) Mill.; žlahtna jablana; križanci; morfometrija